Care providers’ view of the barriers in providing care for adolescents with emotional and behavioral problems - Paclikova, Katerina; Dankulincova Veselska, Zuzana; Madarasova Geckova, Andrea; Tavel, Peter; Jansen, Danielle E. M. C.; van Dijk, Jitse P.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2024)
ObjectivesEmotional and behavioral problems (EBP) during adolescence are a major public health issue due to its high prevalence and long-lasting consequences. The knowledge of the barriers in providing psychosocial care can be a starting point for subsequent efficiency improvement. Therefore, the aim of this study is to assess which barriers do care providers experience while providing psychosocial care for adolescents with EBP.MethodsWe performed a qualitative assessment that was embedded in the Slovak Care4Youth study mapping the system of care provided for adolescents with EBP. We conducted 25 semi-structured individual and group interviews with a total of 49 care providers from 17 institutions that provided preventive counselling, social, and mental healthcare for adolescents with EBP. We focused on the care provider’s perception of barriers in providing care for these adolescents. The interviews were audiotaped and transcribed verbatim. We coded the data using the consensual qualitative research approach in combination with conventional content analysis.ResultsWe found that care providers experienced several barriers in providing care for adolescents with EBP which relate to six themes—legislative framework and legislative changes; financing of the care system; coordination of care; workforce development, education, methodical guidance and supervision; personnel and institutional capacities; and administrative burden.ConclusionAddressing these barriers within the care system from the “front line” perspective provides clues to efficiently improve the psychosocial care for adolescents with EBP. According to the care providers, the organization and financing of the care system requires adaptation; the burden of the care providers should be reduced; and care providers require quality practical education, training, and methodological guidance.